2020
DOI: 10.1186/s13052-020-00916-2
|View full text |Cite
|
Sign up to set email alerts
|

Metreleptin for the treatment of progressive encephalopathy with/without lipodystrophy (PELD) in a child with progressive myoclonic epilepsy: a case report

Abstract: Background A number of genetic syndromes associated with variants in the BSCL2/seipin gene have been identified. Variants that cause skipping of exon 7 are associated with progressive encephalopathy with/without lipodystrophy (PELD), which is characterized by the development of progressive myoclonic epilepsy at a young age, severe progressive neurological impairment, and early death, often in childhood. Because the genetic basis of PELD is similar to that of congenital lipodystrophy type 2, we hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Another seven female patients between the ages of 15 and 40 years with lipodystrophy (5 patients with CGL1 and 2 patients with acquired generalised lipodystrophy) have commenced regular menses from primary amenorrhea or abnormal menstruation after this therapy [ 96 ]. Finally, in two PELD patients, leptin-replacement therapy delayed the neurological regression and allowed better seizure control [ 119 , 120 ].…”
Section: Human Diseases Caused By Mutations Of Bscl2mentioning
confidence: 99%
“…Another seven female patients between the ages of 15 and 40 years with lipodystrophy (5 patients with CGL1 and 2 patients with acquired generalised lipodystrophy) have commenced regular menses from primary amenorrhea or abnormal menstruation after this therapy [ 96 ]. Finally, in two PELD patients, leptin-replacement therapy delayed the neurological regression and allowed better seizure control [ 119 , 120 ].…”
Section: Human Diseases Caused By Mutations Of Bscl2mentioning
confidence: 99%
“…In 2019, Serino et al [ 89 ] published the case of a child with CGL2, myoclonic epilepsy, and progressive neurological deterioration due to the variant c.1076dupC (exon 9) in the BSCL2 gene ( Table 1 , patient 21), another condition that could be considered a new form of Celia’s encephalopathy [ 90 ]. This variant would give rise to a premature stop codon in the transcript NM_001122955.3, p.(Glu360*), [CCT (Pro) GAA (Glu) >> CCC (Pro) TGA (*)].…”
Section: Seipin-associated Diseases: the Seipinopathiesmentioning
confidence: 99%
“…Along the same lines, another of the patients with the c.974dupG variant has been receiving metreleptin and fish oil since the age of 6 months and, at the time of writing ( Table 1 , patient 11), at 4.5 years of age, she does not present neurological symptoms, attends preschool and receives speech therapy but otherwise seems to have normal cognition (Dr. Melissa Crocker, personal communication). In addition, recently, Pedicelli et al [ 90 ] have reported that treatment with metreleptin for one year reduced the number of epileptic seizures in an 11-year-old boy with the homozygous c.1076dupC variant [ 89 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Reduced leptin secretion contributes to the pathogenesis of lipodystrophy by adversely affecting appetite control, glucose and lipid homeostasis and metabolism (16,17). In later stages of the disease, symptoms can include severe metabolic abnormalities (e.g., severe insulin resistance and difficult-to-treat diabetes, severe hypertriglyceridemia) and endorgan complications (e.g., non-alcoholic steatohepatitis (NASH), nephropathy, pancreatitis, cardiovascular disorders, neuromuscular system abnormalities) (1,14,15,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%